2009
DOI: 10.1111/j.1365-2966.2008.14063.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-luminosity gamma-ray bursts as a distinct GRB population: a firmer case from multiple criteria constraints

Abstract: The intriguing observations of the Swift/Burst Alert Telescope (BAT) X-ray flash (XRF) 060218 and the BATSE-BeppoSAX gamma-ray burst GRB 980425, both with much lower luminosity and redshift compared to other observed bursts, naturally lead to the question of how these low-luminosity (LL) bursts are related to high-luminosity (HL) bursts. Incorporating the constraints from both the flux-limited samples observed with Compton Gamma-ray Observatory (CGRO)/BATSE and Swift/BAT and the redshift-known gamma-ray burst … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 71 publications
9
128
3
Order By: Relevance
“…After describing the observational properties of the above sub-classes, their interpretation within the IGC paradigm, the NS-NS merger scenario and the fireshell scenario, we present some prototypes (see Sections 4,5,6,7,8,and 9,respectively). We then proceed in Section 10 to estimate their observed occurrence rates and to compare and contrast our results with those outlined in the literature (see, e.g., Soderberg et al 2006;Guetta & Della Valle 2007;Liang et al 2007;Virgili et al 2009Virgili et al , 2011Rangel Lemos et al 2010;Wanderman & Piran 2010Kovacevic et al 2014;Sun et al 2015). We then draw some general conclusions in Section 11.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…After describing the observational properties of the above sub-classes, their interpretation within the IGC paradigm, the NS-NS merger scenario and the fireshell scenario, we present some prototypes (see Sections 4,5,6,7,8,and 9,respectively). We then proceed in Section 10 to estimate their observed occurrence rates and to compare and contrast our results with those outlined in the literature (see, e.g., Soderberg et al 2006;Guetta & Della Valle 2007;Liang et al 2007;Virgili et al 2009Virgili et al , 2011Rangel Lemos et al 2010;Wanderman & Piran 2010Kovacevic et al 2014;Sun et al 2015). We then draw some general conclusions in Section 11.…”
Section: Introductionmentioning
confidence: 83%
“…In Section 10, we introduce the procedure outlined in Sun et al (2015) for estimating the local rates and their evolution with the redshift of the above sub-classes of long and short bursts, assuming no beaming (note: the recent observation of the absence of GeV emission associated to a BdHN may limit this assumption). By ignoring possible redshift-evolution of the GRB sub-classes luminosity functions and assuming that the GRB cosmic event rate density is redshift-independent (e.g., f (z) = 1), the above method duly takes into account observational constraints, i.e., the detector solid angle coverage of the sky Ω and sensitivities which in turn define a maximum volume of observation depending on the intrinsic luminosity of the sources (see Section 10 and Soderberg et al 2006;Guetta & Della Valle 2007;Liang et al 2007;Virgili et al 2009Virgili et al , 2011Rangel Lemos et al 2010;Wanderman & Piran 2010Kovacevic et al 2014;Sun et al 2015 for details). We obtain:…”
Section: S-grbsmentioning
confidence: 99%
“…On the other hand, the almost continuous distribution of energy releases may indicate that all events are part of a single population that can be described by a single power-law luminosity function. A deeper analysis is beyond the scope of this paper, but it would require an estimation of the true rate of these events, similar to what has been done for the local universe SN events (Pian et al 2006;Soderberg et al 2006b;Liang et al 2007a;Guetta & Della Valle 2007;Virgili et al 2009). …”
Section: A New Population Of Low-luminosity Grbs At Low Redshifts?mentioning
confidence: 99%
“…Early hints to the existence of distinct populations of gamma-ray transients (e.g., Mazets et al 1981;Norris et al 1984), and at least two classes of short-hard (Type-I) & long-soft (Type-II) GRBs (Dezalay et al 1992) have now been extensively corroborated and confirmed by the prompt-emission data E-mail: amir@physics.utexas.edu (AS); nemiroff@mtu.edu (RJN) from independent gamma-ray detector missions (e.g., Kouveliotou et al 1993a;Gehrels, Ramirez-Ruiz & Fox 2009; or follow-up observations of the afterglows or host galaxies (e.g., Zhang et al 2009;Berger 2011Berger , 2014. Although the possibility of more than two classes of GRBs with distinct progenitors has been extensively discussed and considered (e.g., Horvath 1998;Mukherjee et al 1998;Hakkila et al 2001;Balastegui, Ruiz-Lapuente & Canal 2001;Hakkila et al 2004b;Horvath et al 2006;Gehrels et al 2006;Chattopadhyay et al 2007;Horvath et al 2008;Virgili, Liang & Zhang 2009;Gao, Lu & Zhang 2010;Horvath et al 2012;Levan et al 2014;Kbori et al 2014), it has remained a matter of debate and speculation to this date (e.g., Hakkila et al 2000cHakkila et al ,a,b, 2003Hakkila et al , 2004aShahmoradi 2013b;Zhang et al 2014;Levan et al 2014).…”
Section: Introductionmentioning
confidence: 99%